The Conundrum to Wear Religious Uniform in Indonesia: International Human Rights Law and Islamic Law Perspective - Sefriani, Sefriani; Putro, Yaries Mahardika; Putra, Jaya Indra Santoso; Monteiro, Seguito (Universitas Negeri Semarang, 2024)
This study aims to analyze the annulment of the Joint 3 (three) Ministerial Decree concerning School Uniforms for Students, Educators, and School Personnel by the Indonesian Supreme Court and to examine the Supreme Court’s decision under international human rights law and Islamic law. In the annulment of the Joint 3 (Three) Ministerial Decree on School Uniforms for Students, Educators, and School Personnel by the Indonesian Supreme Court, the legal reasoning follows a meticulous analysis rooted in normative legal research. The study employs statutory, conceptual, and comparative approach to unravel the complexities surrounding the decree. Through the descriptive analysis, it is established that the decree runs afoul of the educational values enshrined in the National Education System Act, particularly the imperative to foster religious spiritual strength in students. Moreover, the National Education System Act also mandated that the Indonesian National Education must also be rooted in religious values. The Supreme Court’s decision to annul the Joint 3 (Three) Ministerial Decrees grounded in the rationale that the decree conflicts with the higher law, specifically the National Education System Act. The annulment also aligns with international human rights law and the values of Islamic law. Indonesia has a margin of appreciation in the regulation of religious freedom as practiced in the European Court of Human Rights, adjusting to the condition that Indonesia is not a secular country but also not a religious country. Indonesia is based on Belief in the one and only God and upholds pluralism.